Performance evaluation of FKM central unit air condition system/chilled water system - Amir Hamzah, Azahar (2010)
Air conditioning system has been introduced in past several decades in order to serve comfort condition to the humans. Air conditioner is defined as control air movement, temperature, humidity and cleanliness in a needed space. Meanwhile chilled water is to control the movement of water, air, fluid flow and temperature from chiller plant room. There are several types of system where hot air can be removed from a system in the process of refrigeration and air conditioning. Basic air-conditioning systems and chilled water covers four main components including compressor, condenser, throttling valve and evaporator. The process of heat removal can be done by heat transfer directly or indirectly. Since the system been introduced, performance of the system will be the main issues and until now there are many researches still ongoing in order to get the best performance of air conditioning system. Faculty of Mechanical engineering (FKM) in Pekan has started its operation in July 2009 and almost building in the faculty is occupied with air conditioning system. The type of air conditioning system in the faculty is central unit air conditioning system. The performance of the air conditioning system in the faculty becomes an interesting part to be studied to those who are in that field. An informal interview was conducted with officials from the Jabatan Pembangunan dan Pengurusan Harta (JPPH) that is responsible for monitoring this air conditioning system. The problem that arises in the central air conditioning system in the FKM are influences JPPH to cooperate in order to help an individual for analyzing the performance of air conditioning system.The objective of this project is to review the working system and analyze the performance of air conditioners and chilled water system for daily use. In addition, evaluation and review of cooling load is also taken into account for two rooms, specifically name by Computer Lab and Excellent Centre. The heat gain analysis is compulsory conducted in order to estimate performance of central unit air conditioning system. The heat gain for the Computer Lab and Excellent Centre is calculated to be 23.297kW and 39.952kW respectively. Different condition of date were taken and been analyzed which is performances of the system using single chiller running alternately and two chiller running simultaneously. The result shows that when the system is being operated with single chiller simultaneously, the total available cooling capacity can be ranging between 770kW to 810kW. Whereas for two chiller operations, the total available cooling capacity by the chiller is 1246.77kW. The room total load capacity with single chiller in operation alternately, the value load capacity for Computer Lab is ranging from 18.072kW to 20.482kW and for Excellent Centre is 26.746kW to 27.981kW. While for two chiller operations simultaneously, the room total load capacity for Computer Lab is 25.301kW and for Excellent Centre is 42.168kW. It can be conclude that air conditioning system running with single chiller operation is not enough to absorb the heat gain in the particular room in the present of study. Therefore, the system with 2 chiller operation is the best to meet the needs and more systematic guide for the consumer at Faculty of Mechanical Engineering (FKM) in Pekan. Study also emphasizes the relationship between temperature, pressure, flow rate, the amount of cooling and performance of work for each component and total components involved.